Promoting intercultural education through textbooks of Portuguese language - Balula, João Paulo (2015)
The growing importance of efforts to ensure respect for issues of difference calls for the evaluation of the contribution of textbooks of Portuguese in the promotion of interculturality. We discuss some results of a multi-methodological research that was based on the analysis of two textbooks of Portuguese (4th grade) to implement didactic interventions in a class of the same grade level. The results show that the activities promoting critical thinking about interculturality are scarce in the textbooks analysed and indicate that the role of the teacher is substantial in promoting mutual understanding and respect for the Other.